(untitled) (Journal of the College of Basic Education, 2022)
There is no doubt that the issue of the races and the purity of the species and their interaction with each other is an issue that has occupied many and many researchers, and they have all sought to address this phenomenon, each according to its specialization and orientations. In our research, we seek to shed more light on the concept of naturalization and its relationship to the short story in Iraq after 2003, by overlapping the story with Arabic poetry and the novel. On this basis, I divided my research into an introduction and two chapters that made up an engineering whole. The introduction came to show the research problem, its importance and the research plan. As for the first chapter, it has been titled: Naturalization for Arabs and Westerners. The second chapter was devoted to the interplay of the short story in Iraq after 2003 with the novel, and the conclusion came summarizing the most important research findings